2021
DOI: 10.1002/ffj.3670
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, odour characteristics, and antibacterial activity of optically active cognac lactones

Abstract: In this study, all stereoisomers of cognac lactone (1) were synthesized with over 99% enantiomeric excess via diastereomeric resolution using N‐benzyloxycarbonyl‐l‐proline (N‐Cbz‐l‐proline) as a resolving agent. N‐Cbz‐l‐proline could be applied for the diastereomeric resolution of both syn‐ and anti‐forms and yielded all diastereomers in over 99% diastereomeric excess. The odour properties of racemic and optically active 1 were evaluated for their orthonasal aromas. All the stereoisomers had different odour ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 39 publications
0
0
0
Order By: Relevance
“…We previously reported that N-Cbz-L-proline is an efficient agent for diastereomeric resolution 13,14,26) . (±) -2a-2f were esterified with N-Cbz-L-proline to give a mixture of diastereomer esters 3a-3f (Scheme 2) .…”
Section: Diastereomeric Resolution Of (±) -2 and Lactonizationmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously reported that N-Cbz-L-proline is an efficient agent for diastereomeric resolution 13,14,26) . (±) -2a-2f were esterified with N-Cbz-L-proline to give a mixture of diastereomer esters 3a-3f (Scheme 2) .…”
Section: Diastereomeric Resolution Of (±) -2 and Lactonizationmentioning
confidence: 99%
“…1) . Because lactones exhibit antimicrobial activities 10−12) , we previously reported the antimicrobial activities of optically active whisky and cognac lactones against S. aureus 13,14) . Although γ -alkyllactones are typically used in perfumes, these lactones (1a-1f) can be used in new applications if they Abstract: Six optically active (Z)-7-decen-4-olide derivatives (1a-1f) were synthesized in 99% enantiomeric excess using diastereomeric resolution.…”
mentioning
confidence: 99%